EFFECT OF BIRTH NUMBERS AND PREGNANCY PERIODS ON SOME BLOOD PARAMETERES OF AWASSI EWES - Hussein, A. T.; Khalil, R. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to investigate the effects of birth number, pregnancy stage (pre- and post-pregnancy), and their interaction on selected blood parameters in local Awassi ewes under grazing conditions. The experiment involved 33 local Awassi ewes, divided equally into three groups: the first group consisted of ewe lambs, the second group included ewes with one previous birth, and the third group comprised ewes with multiple births (2–3). Birth number showed no significant effect on any of the blood parameters. However, mean corpuscular hemoglobin concentration (MCHC), hemoglobin (Hb), and packed cell volume (PCV) were significantly higher at mid-pregnancy (12th week) compared with the 4th and 20th weeks of pregnancy. Serum total protein and cholesterol levels were significantly higher (P ≤ 0.01) during the pre-pregnancy period compared with other stages. Serum calcium levels were significantly higher (P ≤ 0.01) during the pre-pregnancy period and at the 4th week of pregnancy compared with the other stages. Phosphorus concentrations increased significantly (P ≤ 0.01) at the 4th week of pregnancy compared with all other study periods. However, no significant interactions were observed between birth number and pregnancy stage. In conclusion, the pre-pregnancy period had a critical impact on certain blood parameters of local Awassi ewes.